2011
DOI: 10.1007/s11832-010-0324-0
|View full text |Cite
|
Sign up to set email alerts
|

Continued growth of the hip after fixation of slipped capital femoral epiphysis using a single cannulated screw with a proximal threading

Abstract: Fixation of the epiphysis using proximally threaded screws allows the preservation of femoral neck growth. The cannulated screw with proximal threading seems to be a safe and relevant implant to help to restore a close-to-normal hip at skeletal maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 32 publications
2
36
1
3
Order By: Relevance
“…The premature physeal closure leads to modifications of the epiphyseal–metaphyseal complex which itself becomes a cause of impingement [ 30 , 32 ]. To avoid this complication, it is necessary to use a type of in situ fixation device which allows continued physeal growth [ 13 , 18 21 ]. Immediate arthroscopic osteoplasty as Leunig et al (2010) [ 11 ] proposed might not be necessary if the initial treatment is done using such a device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The premature physeal closure leads to modifications of the epiphyseal–metaphyseal complex which itself becomes a cause of impingement [ 30 , 32 ]. To avoid this complication, it is necessary to use a type of in situ fixation device which allows continued physeal growth [ 13 , 18 21 ]. Immediate arthroscopic osteoplasty as Leunig et al (2010) [ 11 ] proposed might not be necessary if the initial treatment is done using such a device.…”
Section: Discussionmentioning
confidence: 99%
“…To reach this target, an ideal method in SCFE should stabilize the epiphysis without causing unwanted premature closure of the physis. Histologic, ultrastructural, and clinical studies post stabilization reported remodeling with normalization of the physis [ 15 21 ]. Remodeling due to the growth of the neck can reduce or eliminate head/neck incongruities.…”
Section: Introductionmentioning
confidence: 99%
“…As secondary loss of fixation is rarely observed when screws are used instead of pins, screw fixation has increasingly been performed in SCFE in recent years. Recent studies suggest that the damage to the physis caused by screw fixation might be far less than assumed previously [15][16][17], although no results have been published on prophylactic fixation of the contralateral asymptomatic hip. The aim of this retrospective matched-pair study was to compare the longitudinal growth of the femoral neck and accompanying deformities such as coxa vara in patients with screw fixation with those with Kirschner-wire (K-wire) fixation of the asymptomatic contralateral hip in SCFE.…”
Section: Introductionmentioning
confidence: 87%
“…Die Gleitschraube bietet eine sichere und dauerhafte Stabilisierung der Kopfepiphyse, fördert jedoch im Gegensatz zu den im angloamerikanischen Bereich verwendeten Zugschrauben nicht den vorzeitigen Verschluss der Wachstumsfuge [1]. In der untersuchten Patientenkohorte wurde in keiner der beiden [4] als auch Hackenbroch et al [1] keinen Unterschied in der ATD zwischen erkrankten und prophylaktisch versorgten Hüften mit Gleitschraubenversorgungen. Hinsichtlich weiterer Implantatversorgungen di- vergieren die Angaben von geringen [6] bis sehr starken Verminderungen der ATD [3].…”
Section: Hüftkopfdeformierungunclassified
“…Die damit einhergehende Wiederherstellung der Hüftfunktion und Reduktion des Risikos späterer degenerativer Veränderungen ist mit der Notwendigkeit der Komplikationsvermeidung wie avaskulärer Nekrosen und Chondrolysen verbunden [2,3]. Obwohl eine Vielzahl konservativer Behandlungsmöglichkeiten beschrieben wurde [4], wird die operative In-situ-Fixation mit Stabilisierung der oberen Femurepiphyse mehrheitlich befürwortet. Dennoch wird die Art und Weise der operativen Stabilisierung weiterhin kontrovers diskutiert [5], ebenso die Frage, ob man ein weiteres Wachstum der Fuge zulassen [6] oder einen möglichst zügigen Fugenschluss anstreben sollte [7].…”
unclassified